(untitled) (Economic studies journal, 2020)
This study aims to know the percentage of external flows in Algeria during the period from 1970 to 2018, as well as to measure the correlation and causal relationship between these different flows using time series data. We found through this study that there is a direct relationship between the percentage of workers’ remittances abroad and foreign aid, while the relationship between the rests of the financial flows in Algeria turned out to be weak. On the other hand, it was found through this study that there is no two-way causation between the various financial flows in Algeria, and the causality was limited to one direction from foreign direct investment to foreign debt, from foreign aid to imports, and from exports to foreign aid